General overview on Cellulose and Cellulose Nanocrystals: properties, extraction, application, and sustainable development - Danial, Wan Hazman; Mohd Taib, Raihan; Abu Samah, Mohd Armi; Abdul Majid, Zaiton (Springer Nature, 2022)
This chapter describes the general overview on cellulose and cellulose nanocrystals (CNCs). Structure and properties of cellulose and CNCs are fundamentally discussed in detail. A brief discussion on various techniques and methods of extraction of cellulose and CNCs from a myriad range of precursors such as plants and waste materials are also presented and the applications of cellulose and CNCs in a multitude of fields are described. The sustainable development associated with cellulose and nanocellulose material is also highlighted.